Bank Competition, Risk, and Asset Allocations - Boyd, John (IMF Working Papers; Working Paper, 2009)
We study a banking model in which banks invest in a riskless asset and compete in both deposit and risky loan markets. The model predicts that as competition increases, both loans and assets increase; however, the effect on the loans-to-assets ratio is ambiguous. Similarly, as competition increases, the probability of bank failure can either increase or decrease. We explore these predictions empirically using a cross-sectional sample of 2,500 U.S. banks in 2003, and a panel data set of about 2600 banks in 134 non-industrialized countries for the period 1993-2004. With both samples, we find that banks' probability of failure is negatively and significantly related to measures of competition, and that the loan-to-asset ratio is positively and significantly related to measures of competition. Furthermore, several loan loss measures commonly employed in the literature are negatively and significantly related to measures of bank competition. Thus, there is no evidence of a trade-off between bank competition and stability, and bank competition seems to foster banks' willingness to lend.